ARTERIAL PULSE WAVEFORM AND ESTIMATION OF BLOOD PRESSURE - Osman, Hala Hatim (IRC, 2016)
The correlation between human blood pressure and pulse waveform was clearly observed for long time ago in the medical field. However till today the measurements of the blood pressure and heart rate are recorded by two different devices. This project proposed technique to estimate the continuous blood pressure based on the pulse waveform. The conventional cuff blood pressure monitor provides accurate measurement. However, this method of measurement lacks of continuity as the monitor composed of an inflatable cuff used to restrict the flow of blood, the cuff needs inflation and deflation, thus, it can’t provide continuous and beat to beat measurement. To solve this problem, the proposed method provides continues measurements of blood pressure as it is mainly base on the pulse waveform.